Culture medium establishment to Morinda citrifolia L. conservation in germoplasm bank in vitro - Pereira dos Santos, Renan; de Macedo Medeiros, Eliana; Oliveira Maciel, Fábio; Gaion Malosso, Milena (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Morinda citrifolia L. is a medicinal plant belonging to the family Rubiaceae and is popularly known as Noni. The fruit juice is rich in immunodulatory polysaccharides against sarcoma-type tumors called Noni-ppt and because of its medicinal properties; this species has been collected indiscriminately from its natural environment. Thus, the objective of establishing a culture medium for slowgrowith storage for the conservation of noni in germplasm bank in vitro is an excellent way to conserve this plant, which is unheard of for this species. For this, explants type nodal segment were inoculated, respectively in complete B5 culture medium, they were diluted in the half and in the fourth part, in addition to several types and concentrations of osmotic growth regulators. After 180 days kept in environment for slow growthstorage, it was verified that the most suitable medium for the maintenance of this species through this technique was the B5/2 added 2% sucrose, 1.0 mg/L BAP and 3,0 mg/L IBA. The highest survival rate, number of shootper buds (1.47a), number of buds per stem (2.27a) and, consequently, the highest multiplication rate (4.07a), of the total absence of callus and height of the shoot adequate to the semestral repetitions, when compared with the other treatments used in this experiment. Thus, we concluded that it is possible to maintain explants type nodal segments in slow growth storage culture medium, aiming the conservation of this species in germplasm banks in vitro.